Phytochemistry of piper betle landraces - Bajpai, Vikas; Kumar, Nikhil; Kumar, Brijesh (Boca Raton : CRC Press, 2020)
Piper betle (betel vine) a pan-Asiatic, tropical plant, whichcan also grow under mild subtropical areas, is essentially grown for leaves which are chewed with array of additives besides slaked lime. The plant is cultivated widely in India and its surrounding areas. Phytochemistry of Piper betel landraces presents a brief on the distribution, historical and cultural aspects, and properties ascribed to this plant in the ancient texts. Phytochemical and pharmacological information has also beenincluded to underscore the importance of this plant in the present time. A detailed account on metabolic profiling employing modern methods is included,such as real-time, direct analysis of the flight mass spectrometric method and chemometric analysis for characterization of the available biodiversity and signatures specific to gender and geographical location. It was also possible to identify the gender of unknown landraces, with the help of principal component analysis. Features: Elaborates on the chemical diversity within Piper betle. Piper betle leaves have mouth freshening antimicrobial compounds. Use of chemical signatures for the identification of different Piper betle landraces, their gender and geographical locations.
OCLC-licensed vendor bibliographic record.
Keywords: Piper betle; Botanical chemistry; MEDICAL / Pharmacology; SCIENCE / Chemistry / General